2009
DOI: 10.1103/physrevlett.102.132001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence forX(3872)ψ(2S)γinB±

Abstract: In a search for B-->cc[over ]gammaK decays with the BABAR detector, where cc[over ] includes J/psi and psi(2S), and K includes K(+/-), K(S)(0), and K(*)(892), we find evidence for X(3872)-->J/psigamma and X(3872)-->psi(2S)gamma with 3.6sigma and 3.5sigma significance, respectively. We measure the product of branching fractions B(B(+/-)-->X(3872)K(+/-))xB(X(3872)-->J/psigamma)=[2.8+/-0.8(stat)+/-0.1(syst)]x10(-6) and B(B(+/-)-->X(3872)K(+/-))xB(X(3872)-->psi(2S)gamma)=[9.5+/-2.7(stat)+/-0.6(syst)]x10(-6).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
75
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 185 publications
(93 citation statements)
references
References 29 publications
17
75
0
1
Order By: Relevance
“…[689], Guo et al studied the radiative decays of the X(3872) into γJ/ψ and γψ using an effective field theory. Their results also suggested that their experimental ratio [89,92] is not in conflict with the hadronic molecular picture that the X(3872) is dominated by the DD * component.…”
Section: Lattice Qcdmentioning
confidence: 68%
See 4 more Smart Citations
“…[689], Guo et al studied the radiative decays of the X(3872) into γJ/ψ and γψ using an effective field theory. Their results also suggested that their experimental ratio [89,92] is not in conflict with the hadronic molecular picture that the X(3872) is dominated by the DD * component.…”
Section: Lattice Qcdmentioning
confidence: 68%
“…Under this molecule picture, Swanson calculated the ratio of B(X(3872) → ψ γ) with respect to B(X(3872) → J/ψγ) to be 4 × 10 −3 [197,219], which largely deviated from the experimental data 3.4 ± 1.4 [89] and 2.46 ± 0.64 ± 0.29 [92]. He derived the ratio of B(X(3872) → γJ/ψ) with respect to B(X(3872) → J/ψπ + π − ) to be around 10 −2 [197,219], while the experimental value is 0.14 ± 0.05 [75] and 0.33 ± 0.12 [89]. Within this model, the ratio of B(X(3872) → D 0D0 π 0 ) with respect to B(X(3872) → J/ψπ + π − ) was inconsistent with experimental data.…”
Section: Molecular Schemementioning
confidence: 69%
See 3 more Smart Citations